2000
DOI: 10.4269/ajtmh.2000.62.200
|View full text |Cite
|
Sign up to set email alerts
|

Genetic isolation by distance among Aedes aegypti populations along the northeastern coast of Mexico.

Abstract: Abstract. A population genetic analysis of gene flow was conducted among 10 Aedes aegypti collections from seven cities along the northeastern coast of Mexico. Four collections were made from Monterrey to examine local patterns of gene flow. Markers included 60 random amplified polymorphic DNA (RAPD) loci amplified by the polymerase chain reaction and single strand conformation polymorphism analysis of variation in a 387-basepair region of the NADH dehydrogenase subunit 4 from the mitochondrial DNA (mtDNA). Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
123
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(139 citation statements)
references
References 50 publications
10
123
1
5
Order By: Relevance
“…Values of expected H were similar to those found previously by de Sousa et al (2001) in several Argentine cities using only 17 RAPD loci. Likewise, levels of variability were similar to those found in other populations from Brazil (Ayres et al 2003, Paduan et al 2006), Puerto Rico (Apostol et al 1996) and Mexico (Gorrochotegui-Escalante et al 2000), using the same molecular markers. Rondán Dueñas (2005) reported that haplotype diversity values at the mitochondrial control region in Ae.…”
Section: Discussionsupporting
confidence: 84%
“…Values of expected H were similar to those found previously by de Sousa et al (2001) in several Argentine cities using only 17 RAPD loci. Likewise, levels of variability were similar to those found in other populations from Brazil (Ayres et al 2003, Paduan et al 2006), Puerto Rico (Apostol et al 1996) and Mexico (Gorrochotegui-Escalante et al 2000), using the same molecular markers. Rondán Dueñas (2005) reported that haplotype diversity values at the mitochondrial control region in Ae.…”
Section: Discussionsupporting
confidence: 84%
“…aegypti and the same ND4 gene region. Gorrochotegui-Escalante et al (2000) found two genetic clusters. The presence of two genetically related groups in Mexico was corroborated by the results of maximum likelihood analyses (ML) that employed a broad sample size (Gorrochotegui-Escalante et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Internal primers were designed to shotgun-amplify the complete 1260-bp cox1 amplicon: two smaller fragments (~700-bp) were assembled following amplification using primers pairs Fly10 27 + coxF1 (5'-TTT GAG CTC ATC ATA TAT TTA-3') and UEA3 41 + coxR2 (5'-GCT CGT GTA TCA ACA TCT-3'). Primers ND4+/ND4- 16 were used to amplify the nd4 gene.…”
Section: Mosquitoesmentioning
confidence: 99%